(untitled) (Biological Sciences - PJSIR, 2022)
Four 12-years old trees of Populus euramericana harvested in Faisalabad and Toba Tek Singh Districts were analysed to determine the density distribution in the stem. Density increased with age and increasing height. Minimum density noted was 0.25 g/cm" and maximum density was 0.56g/cm3.